2017
DOI: 10.4103/abr.abr_267_16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Levothyroxine on Serum Levels of Interleukin 10 and Interferon-gamma in Rat Model of Multiple Sclerosis

Abstract: Background:There is an increase in inflammatory and a reduction in anti-inflammatory cytokines in multiple sclerosis (MS). Considering the role of thyroid hormones in the development and regulation of both neural and immune systems, the aim of this study was to evaluate the effects of levothyroxine on serum concentrations of interleukin-10 (IL-10) and interferon gamma (IFN-γ) in animal models of MS.Materials and Methods:To induce demyelination in male Wistar rats, lysolecithin was injected into the optic chias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[ 5 ] Recent studies in Iran have reported that the prevalence of this cancer among Iranian women has reached 22% and unfortunately the age of onset of this disease in Iranian women is 10–15 years less than the age of onset in Western countries. [ 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%